Dropping/Withdrawing Semesters among Preparatory Year Engineering Students at King Abdulaziz University, KSA - Salameh S. Mahmoud; Khalil Al-Basyouni (Archives of Current Research International, 2024)
Dropping/drawing semesters in all academic institutions and the faculty of engineering in KAU/KSA becomes a very common phenomenon recently. This issue threatens time to graduation and delay students plans to finish and get jobs and start their life after graduation successfully. To study this phenomenon, the researchers chose all preparatory year engineering university students in the Kingdom of Saudi Arabia as a population and 100 students from the faculty of engineering at King Abdulaziz University as a sample. This study investigates the reasons behind dropping/withdrawing semesters. To this end the researcher designed a sixteen-item questionnaire and distributed it to the preparatory engineering students at KAU. The findings of the study revealed different reasons behind dropping/withdrawing semesters. These reasons fall under three categories: academic, managerial, and social. According to the respondents, the social reasons were the most influential compared to other reasons. The study recommends that the university reconsiders some polices to make the students’ university life enjoying and more relaxing.